Morbilliform skin rash with prominent involvement of the palms in Chikungunya fever. (2018) - Tini, Maria Laura; Rezza, Giovanni
Abstract: An outbreak of chikungunya occurred in Central Italy in the summer of 2017. During the outbreak, two siblings with fever and joint pain developed a morbilliform skin rash with prominent involvement of the palms. Knowledge of the characteristics of chikungunya exanthem is important to adddress clinical diagnosis.